Monitored-based methodology to predict the initiation of corrosion in RC structures - Tantele, Elia; Votsis, Renos; Onoufriou, Toula (My University, 2015)
The corrosion of steel reinforcement in RC structures is the main deterioration factor of these structures and the employment of SHM techniques can provide indications on the corrosion activity at its early stages. In this study, a methodology is proposed to predict the initiation of corrosion on RC structures using information from SHM data in order to alleviate the impact of uncertainties currently employed in theoretical corrosion models. The monitored data are obtained from the half-cell potential and the concrete resistivity methods. In the methodology the data processing is combined with condition rating and risk assessment principles in order to assess the current structural condition and predict when corrosion initiation is due. The results show that the proposed methodology can provide information on the timeframe of the corrosion state of RC members and most importantly before its effect are visible and the repairing work is mandatory and costly.
Keywords: Data handling; Forecasting; Offshore pipelines; Risk assessment